Comparative Anatomical Study of Leaves in Five Cupressaceae Gray. Taxa in Kurdistan Region - Iraq - Yousif, Ibrahim Z.; Shahbaz, Saleem E. (Science Journal of University of Zakho, 2023)
This study investigates the leaf anatomy of five Cupressaceae taxa in the Kurdistan region-Iraq. Using the light microscope for numerical and descriptive anatomical variations of three species and two varieties belonging to Cupressus, Platycladus, and Juniperus genera were examined for Taxonomic value. These include the characters of epiderm, hypoderm, mesophyll layer, resin canals, transfusion tracheids, pith, and vascular bundles. There are significant differences among studied species and genera. Cupressus taxa exhibit a similar cross-sectional outline. Cupressus arizonica has a larger resin canal (125.4 µm) and longer palisade cells (91.8×27 µm) compared to C. sempervirens varieties. Platycladus orientalis form a wide rhombic outline, with an abaxial resin canal similar to Juniperus oxycedrus and C. arizonica. J. oxycedrus has a triangle outline with a thick hypoderm that extends below the entire epiderm, except under stomatal depressions. While in Cupressus and Platycladus taxa, the hypoderm is restricted only to the abaxial surface of the leaf. J.oxycedrus lacks pith entirely, unlike Cupressus and Platycladus taxa where they form polygonal or slightly straight pith at the center of the vascular bundle.